Prediction of Uplift Capacity of Belled-type Pile with Shallow Foundation in Sandy Ground - J-G. Kang; N. Yasufuku; R. Ishikura; A. Y. Purnama (International Association of Lowland Technology, 2019)
This paper describes a semi-empirical model for predicting the uplift resistance of a belled-type pile considering the relative density of the ground. The variable parameters were utilized in the model are the pile length, the diameter of pile tip, the diameter of pile, and the angle of internal friction in the ground. Moreover, the inclination angle of pile tip and the relative density of the ground, which are not studied in the previous researches, were considered. In this study, an experimental model was conducted with various conditions such as the relative density of the ground and the inclination angle of pile tip those are designated to determine the failure surface of the ground. Based on results, a new model which can be applied to the belled-type pile was proposed by improving the limit equilibrium equation in the previous models. In addition, to confirm the reliability of the newly proposed a model of limit equilibrium equation of the belled-type pile, the models which are presented in the previous studies were compared with the proposed model. Consequently, the proposed model in this study correspond the higher reliability in comparison with the previous models.